Inhibition of Thrombin, Plasmin and Plasminogen Activation by Amidino Compounds - Geratz, J. D (Thrombosis and Haemostasis, 1970)
1. A series of amidino compounds have been investigated for their inhibitory effect on thrombin, plasmin and the streptokinase dependent activation of plasminogen. Diamidines composed of two amidinophenyl residues linked in para or meta position by a molecular bridge proved to be the strongest inhibitors known so far of the three enzyme systems, and they were much more active than amidines with a single-ring structure.2. Of all the compounds tested, pentamidine was the most effective inhibitor of the hydrolysis of BANA by thrombin and plasmin. The Ki values were 9 × 10-6 M and 3.3 × 10-6 M, respectively. Inhibition was competitive in nature.3. Pentamidine was the leading inhibitor of the fibrinolytic activity of plasmin and was approximately 83 times stronger, on a molar basis, than ε-aminocaproic acid.4. Pentamidine also possessed the greatest inhibitory effect on the streptokinase-mediated activation of human plasminogen. On a molar basis pentamidine was 910 times more active than ε-aminocaproic acid.5. In the thrombin clotting test, some amidines caused inhibition while others brought about an acceleration of the reaction. M & B 4596 was the strongest inhibitor affecting 50% inhibition at a concentration of 5 × 10-6 M. 2.2’-Dibromopropamidine produced the greatest augmentation of thrombin activity, raising it 167% above the control level at a concentration of 2 × 10-4 M.6. The caseinolytic activity of thrombin again was blocked most effectively by M & B 4596. All other amidines also proved inhibitory in this assay system.